2021
DOI: 10.1037/sgd0000409
|View full text |Cite
|
Sign up to set email alerts
|

Examination of minority stress pathways to suicidal ideation among sexual minority adults: The moderating role of LGBT community connectedness.

Abstract: Individuals identifying as sexual minorities are at heightened risk for suicidal ideation and attempts. Meyer’s (1995, 2003) minority stress model proposes that external minority stressors (i.e., harassment, rejection, discrimination) result in the internalization of these negative attitudes and beliefs, which then leads to psychological distress (e.g., suicidal thoughts). However, the role of potential resiliency factors, such as connectedness to the LGBT community, remains less explored. This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 74 publications
0
19
0
2
Order By: Relevance
“…This finding is of particular concern. Young people who belong to gender and sexual minority groups frequently report suicidal ideation at much higher rates than their cisgender and heterosexual counterparts [ 34 ]. A recent study suggested that feelings of community connectedness among 2SLGBTQ+ youth is an important protective factor against suicidal ideation and the progression of poor mental health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is of particular concern. Young people who belong to gender and sexual minority groups frequently report suicidal ideation at much higher rates than their cisgender and heterosexual counterparts [ 34 ]. A recent study suggested that feelings of community connectedness among 2SLGBTQ+ youth is an important protective factor against suicidal ideation and the progression of poor mental health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Young people who belong to gender and sexual minority groups frequently report suicidal ideation at much higher rates than their cisgender and heterosexual counterparts [ 34 ]. A recent study suggested that feelings of community connectedness among 2SLGBTQ+ youth is an important protective factor against suicidal ideation and the progression of poor mental health [ 34 ]. The understanding that much of the community connectedness youth were experiencing before the pandemic has been removed due to physical distancing requirements, along with the heightened prevalence of suicidal ideation among these groups in general, points to the need for mental health services to be accessible and sufficient for youth in these groups [ 5 , 7 , 14 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every participant was asked to rate Item 20 and any participant who had previously attempted suicide was requested to rate Item 21 ( 28 ). The BSS has also been used in a number of Western ( 29 ) and non-Western ( 30 ) studies to measure suicidal ideation among LGB individuals. Its internal consistency reliability in these studies ranged from α = 0.81 to 0.95 ( 29 – 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…The BSS has also been used in a number of Western ( 29 ) and non-Western ( 30 ) studies to measure suicidal ideation among LGB individuals. Its internal consistency reliability in these studies ranged from α = 0.81 to 0.95 ( 29 – 30 ). In this study, the scale score yielded an excellent internal consistency reliability of α = 0.97.…”
Section: Methodsmentioning
confidence: 99%
“…Otra investigación, esta vez realizada en Australia con familiares de personas LGTBI+ que habían fallecido por suicidio, encontró que las víctimas presentaban puntuaciones altas de estigma internalizado y vergüenza, así como una baja autoaceptación, entre otra sintomatología (Skerrett et al, 2016). Del mismo modo, Cain et al (2017), con una muestra de hombres gais y bisexuales de Estados Unidos, encontraron que un mayor estigma internalizado estaba asociado con mayores síntomas depresivos; y Rogers et al (2021), en un estudio con población con una orientación sexual minoritaria de Estados Unidos, observaron que niveles mayores de estigma internalizado estaban asociados con mayor ideación suicida. Por último, en un trabajo chileno con adultos homosexuales se observó que el estigma internalizado estaba asociado con mayores niveles de sintomatología ansioso-depresiva, así como con menores niveles de satisfacción con la vida (Gómez et al, 2021).…”
Section: Estigma Internalizado Y Aceptación De La Propia Orientación ...unclassified